2021
DOI: 10.1177/17496020211023318
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Netflix Original’ and what it means for the production of European television content

Abstract: The European audiovisual market has unique contextual characteristics that constrain the sustainability and development of audiovisual content. Among other shifts, the rise of global subscription video-on-demand players like Netflix have been reshaping this market. Although Netflix has been investing in Europe, little is known about their actual investment strategies. This study’s goal is to analyse Netflix original investment in European scripted series and examine their implications for the European market. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 30 publications
0
26
0
2
Order By: Relevance
“…Research into Netflix catalogues in Europe has shown that the large majority of their offerings still consist of Anglo-Saxon productions (EAO, 2020b; Iordache, 2021). Nevertheless, the data also shows a shift in the investments made in Netflix original content, which has become considerably more diverse in terms of language and country of origin, in the past years (Afilipoaie et al, 2021).…”
Section: Transnational Television: the Space Betweenmentioning
confidence: 98%
See 1 more Smart Citation
“…Research into Netflix catalogues in Europe has shown that the large majority of their offerings still consist of Anglo-Saxon productions (EAO, 2020b; Iordache, 2021). Nevertheless, the data also shows a shift in the investments made in Netflix original content, which has become considerably more diverse in terms of language and country of origin, in the past years (Afilipoaie et al, 2021).…”
Section: Transnational Television: the Space Betweenmentioning
confidence: 98%
“…Previous research has identified four categories of Netflix Originals in Europe (Afilipoaie et al, 2021), based on the type of investment: (1) licenced deals; (2) co-production/co-financing deals; (3) full Netflix Originals; and (4) continuation deals. We will structure our analysis mainly on the first three categories, but we found all four useful in tracing the different types of Netflix investments in Europe over time, as they point to different characteristics of transnationalisation, whether through temporary or long-term strategies.…”
Section: Transnationalisation Through the Netflix Originalmentioning
confidence: 99%
“…In its attempt to level the playing field between powerful US streaming platforms active in European markets, and local or regional players, the 2018 revision of the Audiovisual Media Services Directive imposed a 30% European quota on on-demand audio-visual players, enhanced prominence demands, and allowed Member States to extend investment obligations to on-demand service providers, also when targeting a foreign market. Although there is evidence to suggest that Netflix was already investing in European content before the provisions were implemented (Afilipoaie, In press), they may be relevant in the European expansion of other “Streaming Wars” protagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Original European content has also received growing investments from the platform, with more and more titles announced for the coming year (Thomson 2020). Defining the Netflix Original has not been an easy task, as the company has been continuously diversifying its strategies (Afilipoaie et al In press; Petruska and Woods 2019). Four types of investments have been identified in the European markets: (1) licensed originals, (2) continuation deals, (3) co-production/co-financing deals, and (4) “full Netflix Originals,” which are produced and financed entirely by the platform for exclusive rights (Afilipoaie et al In press).…”
Section: Of Flows and Platformsmentioning
confidence: 99%
See 1 more Smart Citation